IMPLEMENTASI PENDIDIKAN LATIHAN DASAR MAHASISWA PECINTA ALAM DALAM PEMBENTUKAN KARAKTER KONSERVASI ANGGOTA DI WILAYAH BEKASI KARAWANG - Daratista, Jeni; Dewi, Ratna Sari; Sutarjo, Sutarjo (IKIP Siliwangi, 2025)
This study aims to describe and analyze the implementation of Basic Training Education (Diklatsar) in Student Nature Lover Organizations (Mapala) in shaping the conservation character of members in the Bekasi Karawang region. The character values examined include environmental awareness, cooperation, responsibility, independence, critical thinking, and their application in daily life. This research is motivated by the lack of character education as a means of instilling conservation values deeply and sustainably among the younger generation. The study employs a descriptive qualitative approach with data collection techniques such as in-depth interviews, observation, and documentation. The research subjects consist of nine informants who are chairpersons, mentors, and active members from three Mapala organizations in Bekasi and Karawang namely Mapalaska, Kapal Baja, and Mapala Petang. The main focus of the study is on three aspects of Diklatsar implementation planning, execution, and evaluation, as well as how these activities shape the members conservation character. The findings reveal that the implementation of Basic Training in these organizations has been structured and oriented towards character development through experiential learning. Thus, Basic Training Education in Mapala serves not only as a model of nature-based youth education but also as an alternative solution for shaping students character in environmental concern, collaboration, responsibility, independence, and critical thinking.